Step-by-step explanation:
This is known as the triple tangent identity. Start with the fact that the three angles add up to 0.
(x − y) + (z − x) + (y − z) = 0
Subtract two terms to the other side and take the tangent:
x − y = -((z − x) + (y − z))
tan(x − y) = tan(-((z − x) + (y − z)))
Use reflection property:
tan(x − y) = -tan((z − x) + (y − z))
Now use angle sum identity:
tan(x − y) = -[tan(z − x) + tan(y − z)] / [1 − tan(z − x) tan(y − z)]
tan(x − y) = [tan(z − x) + tan(y − z)] / [tan(z − x) tan(y − z) − 1]
tan(x − y) [tan(z − x) tan(y − z) − 1] = tan(z − x) + tan(y − z)
tan(x − y) tan(z − x) tan(y − z) − tan(x − y) = tan(z − x) + tan(y − z)
tan(x − y) tan(z − x) tan(y − z) = tan(x − y) + tan(z − x) + tan(y − z)
Answer:
What is countercurrent multiplication? ... Countercurrent multiplication in the kidneys is the process of using energy to generate an osmotic gradient that enables you to reabsorb water from the tubular fluid and produce concentrated urine.
Answer:
12 shirts
Step-by-step explanation:
You cant have one fourth if a shirt so if you have 12 yards with one shirt needing 1 yard you get 12
Direct variation is when one variable changes the other changes in proportion of the first, therefore all the above
With what ??? I don’t see nothing